2021
DOI: 10.1111/bph.15579
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of megadose vitamin C to reverse organ dysfunction in sepsis and COVID‐19

Abstract: Sepsis induced by bacteria or viruses can result in multi-organ dysfunction, which is a major cause of death in intensive care units. Current treatments are only supportive and there are no treatments that reverse the pathophysiological effects of sepsis. Vitamin C has antioxidant, anti-inflammatory, anticoagulant and immune modulatory actions, so is a rational treatment for sepsis. Here we summarise data that support the use of megadose vitamin C as a treatment for sepsis and COVID-19. Mega-dose intravenous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
1
28
0
1
Order By: Relevance
“…Thus, monitoring the immune status of COVID-19 patients is not only helpful for predicting the prognosis of disease but also improves the therapeutic effect. Consistent with this notion, previous studies have shown that the reduction in inflammation parameters and improvement in lymphopenia are common manifestations of effective treatment (47,48). Given that we have drawn the dynamic immunological parameter landscape in COVID-19 patients with different outcomes, these immune indicators could be used to guide treatment strategies.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, monitoring the immune status of COVID-19 patients is not only helpful for predicting the prognosis of disease but also improves the therapeutic effect. Consistent with this notion, previous studies have shown that the reduction in inflammation parameters and improvement in lymphopenia are common manifestations of effective treatment (47,48). Given that we have drawn the dynamic immunological parameter landscape in COVID-19 patients with different outcomes, these immune indicators could be used to guide treatment strategies.…”
Section: Discussionsupporting
confidence: 65%
“… 23 Previous studies have intimated the immunomodulatory, antioxidant, and anti‐inflammatory activities of VC. 24 , 25 , 26 VC has been widely used in treating several inflammatory diseases, especially ARDS and sepsis. 27 , 28 , 29 Severe inflammation and cytokine storm contribute to severe ARDS and subsequent mortality in COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…As in septic sheep, sodium ascorbate reduced plasma creatinine (118 to 84 µmol/L) and increased urine flow (10 to 400 mL/h), and mean arterial pressure was restored despite a complete withdrawal of noradrenaline, at least over the 7 h intervention period [137]. Collectively, these pre-clinical and clinical studies suggest that the optimal dosage, timing and duration of vitamin C therapy are likely to be critical factors that determine its therapeutic efficacy in sepsis, but these factors currently need detailed investigation [120]. Hence, two pilot placebo controlled RCTs are currently underway examining the effects of intravenous mega-dose sodium ascorbate treatment (sodium ascorbate, 60 g and 120 g) on renal outcomes and vasopressor requirements in patients with sepsis (ACTRN12620000651987p; NCT04796636).…”
Section: Vitamin Cmentioning
confidence: 97%
“…Vitamin C is also an important cofactor for the synthesis of endogenous vasoconstrictors such as noradrenaline and vasopressin [116], which may further aid in the circulatory management of patients with sepsis who often become unresponsive to vasopressor therapy. Critically-ill patients have abnormally low plasma ascorbate levels [117][118][119], which is compounded by the inability of humans to naturally synthesis vitamin C, providing another reason for the administration of vitamin C during sepsis [120]. Since enteral uptake is insufficient to normalize plasma ascorbate levels due to saturable intestinal sodium-dependent vitamin C transporters (SVCTs), intravenous treatments are required [121].…”
Section: Vitamin Cmentioning
confidence: 99%